Papers from the Geological Department : Vol. xxii - University of Glasgow. Geological Department (Glasgow : The Department, 1947)
Comprises chiefly reprints from other publications.
Includes Index.
Vols. 10-23 are also numbered as Glasgow university publications, no. 7-8, 10, 20-21, 31-32, 36, 39, 43, 69-71, 88.
Keywords: Geology -- Periodicals; Geology -- Periodicals; Paleontology -- Periodicals